Clinical, myopathological, and genetic features of two Chinese families with Andersen-Tawil syndrome - Wang, Jiaxuan; Qu, Qianqian; Zheng, Xianzhao; Ma, Xiaoli; Cui, Wenhao; Lv, Zheng; Hu, Cong; Li, Shiyao; Zhao, Jiongbo; Lv, Haidong (Frontiers in Neurology, 2024)
Purpose To explore the clinical, muscle pathological, and pathogenic gene mutation characteristics of Andersen-Tawil Syndrome (ATS) and enhance the understanding of ATS among clinical practitioners. Methods Retrospective analysis of clinical data and muscle pathology of two ATS families, along with genetic testing for probands and some family members. Results In Family 1, spanning four generations, four individuals were affected, while Family 2 had two affected individuals across four generations. All six patients in both families experienced onset in childhood, presenting with periodic paralysis, arrhythmias, and craniofacial skeletal abnormalities. In Family 1, the proband’s periodic paralysis was more triggered by low temperature and exercise, occurring several times a year, lasting 4–7 days. All three adult patients in Family 1 had a history of hypokalemia, and the frequency and severity of attacks were reduced after regular oral potassium supplement therapy. Two adult females in Family 1 experienced limb weakness triggered by stress, exertion, and premenstrual period, with milder symptoms than the proband. In Family 2, the proband’s periodic paralysis typically occurred the day after excessive exertion, with a frequency of approximately 2–3 months. Two years prior, the proband developed arrhythmias without palpitations or chest tightness. The proband’s brother experienced intermittent limb weakness during adolescence, remained untreated, and had sudden death at age 40. Physical examination revealed characteristic features in Family 1 and both probands: small mandible, wide eye spacing, and fifth-digit clinodactyly. Four adult patients were shorter in stature, while the growth status of a pediatric patient was indeterminate. Supplementary tests showed a history of hypokalemia during muscle weakness episodes in Family 1, while Family 2 patients had normal potassium levels during episodes. The long exercise tests were positive in both probands. Muscle MRI showed no significant abnormalities, but muscle pathology revealed rimmed vacuoles and tubular aggregates. Genetic testing identified KCNJ2 gene mutations in two probands and some of their family members, with c.407C > T (p.S136F) heterozygous mutation in Family 1 and c.652C > T (p.R218W) heterozygous mutation in Family 2. Conclusion Among the clinical symptoms of the patients with Andersen-Tawil Syndrome in this study, not everyone exhibits the full triad of signs: periodic paralysis is the most common initial symptom, craniofacial and digit skeletal abnormalities are characteristic signs, and ventricular arrhythmias pose the most serious potential risk. Given that these typical symptoms were observed in 5 out of 6 patients, clinicians should pay special attention to these typical symptoms, and patients with these symptoms should be followed up over time. Muscle biopsy May reveal pathological changes such as tubular aggregates, but genetic testing for KCNJ gene mutations remains a crucial diagnostic criterion for this syndrome.